Suicidal behavior in individuals accused or convicted of child sex abuse or indecent image offenses: Systematic review of prevalence and risk factors. Issue 4 (3rd April 2021) - Key, Rebecca; Underwood, Alan; Farnham, Frank; Marzano, Lisa; Hawton, Keith
Abstract: Objective: An emerging body of research indicates that child sex abuse (CSA) offenders are at high risk of suicide when their offenses come to light and that those accused of accessing indecent images of children (IIOC) are at particular risk. Methods: We conducted a systematic review and narrative synthesis on suicide rates and risk factors in this population of offenders. A keyword search of bibliographic databases (PsycINFO, Ovid, MEDLINE, Embase, PILOTS, SCIE, the Cochrane Central Register of Controlled Trials [CENTRAL] and CINAHL) was conducted. Results: Eighteen articles were included in the review, with eleven studies meeting criteria for quality assessment. The risk of suicide in perpetrators of CSA and IIOC might be over 100 times that of the general population, although estimates vary widely between studies. Several complex, interlinking factors were identified as associated with risk, including shame, unique demographic characteristics of the offenders, absence of prior criminal contact, and the impact of a criminal investigation. Conclusions: The review identified factors that may have practical, clinical, and operational implications in the prevention of suicide in CSA and IIOC perpetrators. Exploring the impact of the investigation itself on suicide risk, including potential operational strategies and clinical input to reduce risk, should be a priority.